Opportunities and challenges for mobile crowdsourcing - conceptualisation of a platform architecture. (29th December 2014) - Korthaus, Axel; Dai, Wei
The emergence of a broad variety of effective approaches under the umbrella term 'crowdsourcing', which involves the engagement of potentially large and open crowds of participants for the undertaking of a task, has become a phenomenon that businesses have increasingly taken interest in lately. Given the significant increase in mobile phone penetration and the expansion of existing mobile network capacity, e.g., based on heterogeneous networks (HetNets), new forms of crowdsourcing can be conceived that leverage the mobile and ubiquitous user base. This paper aims to explore some of the opportunities and challenges of new approaches to mobile and ubiquitous crowdsourcing solutions. In addition, we present the conceptual architecture of a context–aware mobile crowdsourcing platform that brings together 'crowdsourcers' as service requesters and 'mobile workers' as service providers.